Is there an association between elongation factor 1-α overdominance in the seastar Pisaster ochraceus and “seastar wasting disease”? - Wares, John; Schiebelhut, Lauren (PeerJ PrePrints, 2015)
In recent years, a massive plague has killed millions of seastars, of many different species, along the Pacific coast of North America. This disease, known as 'seastar wasting disease' (SSWD), is thought to be caused by viral infection. In the affected seastar Pisaster ochraceus, previous work had identified that the elongation factor 1-α locus harbored an intronic insertion allele that is lethal when homozygous yet appears to be maintained at moderate frequency in populations through increased fitness for heterozygotes. The environmental conditions supporting this increased fitness are unknown, but overdominance is often associated with disease. Here, we evaluate seastars from 3 regional populations of P. ochraceus to identify the relationship between SSWD and genotype. Although our data suggest that there may be decreased infection or mortality rates in individuals that are heterozygous at this locus, the effect is small and not statistically significant.
Keywords: disease; genetic diversity; overdominance; polymorphism; Pacific Ocean; Pisaster ochraceus; seastar